Humour-themed holistic learning processes in a Finnish primary school - Aerila Juli-Anna; Rönkkö Marja-Leena; Stenius Tuula (Cracow Tertium Society for the Promotion of Language Studies, 2025)
Although humour in education has shownpositive research results, its use in Finnish classroomsis not common andis notincludedin Finland’s curricula. In this study, pupils’ humour is utilised as part of a holistic learning process in Finnish primary education. Implementing holistic learning processes means focusing on child-centredness, dissolving subject boundaries and concentrating on learning-to-learn skills,overall growth and traditional subject-learninggoals. As a framework for the learning process,this studyfollows the guidelines of theNarratives and Craftsmodel,which aims to connect arts-based activities with different themes. This study aimsto investigate the role of humourin the context of an arts-based learning process andtoassess opportunities for its more conscioususein learning. The data weretakenfrom the outcomes of 36 pupilsduring aholistic learning process and were analysedusing qualitative content analysis. The results indicatedthat creative or arts-based activities and humourworked well together as a means for pupils toincorporatetheir inner thoughts and personal perceptions intotheirassignments. Furthermore, humourcan be asource of a long-term process,and expressions of pupils’ humour can be steered by assignments and preliminary materials,as well as by collaboration with other pupils and the teacher. However, teachers should have more research-based information about humourin the classroom and about the importance of humourin the community and for pupils.